An Iron-NDC Framework with a Cage Structure and an Optothermal Conversion in NIR Window - Bin Tan; Zhao-Feng Wu; Xiao-Ying Huang (Molecules, 2022)
Pursuing novel materials with efficient photothermal conversion under irradiation at the near-infrared region windows (NIR, 750–850 nm; NIR-I and NIR-II, 1000–1320 nm)) is of great importance due to their irreplaceable applications, especially in the biomedical field. Herein, on the basis of a coordination chemistry strategy, an iron-based metal-organic framework (MOF) of [N(CH3)4]2[Fe3(NDC)4]·DMF·3H2O (Fe-NDC, 1,4-H2NDC = 1,4-naphthalenedicarboxylic acid, N(CH3)4+ = tetramethyl-ammonium, and DMF = N,N-dimethylformamide) was prepared and characterized. Due to the d-d transition effect introduced by coordination with the transition-metal ion of iron and the highly conjugated naphthalenic moiety in 1,4-H2NDC, guaranteeing an energy transfer between iron and the organic module, Fe-NDC shows a remarkable broad absorption, which could be extended into the NIR-II section. As a result, Fe-NDC could be irradiated by NIR laser (both 808 and 1064 nm) to achieve photothermal conversion. This work sets a good example to inspire the future designation of NIR light-irradiated photothermal materials based on the first-row transition metals.